2001
DOI: 10.1093/milmed/166.9.791
|View full text |Cite
|
Sign up to set email alerts
|

Forward Surgical Stabilization of Penetrating Lower Extremity Fractures: Circular Casting Versus External Fixation

Abstract: Based on these variables, the authors determined that external fixation is the treatment of choice for penetrating lower extremity fractures in the forward surgical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…External fixation has even been recommended on logistic rather than medical reasons (8). This prospective study reports a very high early complication rate of external fixation and cautions against its universal acceptance.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…External fixation has even been recommended on logistic rather than medical reasons (8). This prospective study reports a very high early complication rate of external fixation and cautions against its universal acceptance.…”
Section: Introductionmentioning
confidence: 81%
“…The use of an external fixator for managing war wounds has been debated, with opinions both for and against its use (4)(5)(6)(7)(8)(9)(10). At the end of the Second World War, Cleveland in a post war summary reported that it was associated with a very high complication rate, and the devices were removed from American military hospitals (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a post war report, Cleveland stated that "its use was associated with a high percentage of both infection and delayed union ... the method was therefore forbidden and removed from the hospitals..." [58]. More recently, based upon an analysis of the conflict in Somalia, external fixation became the preferred stabilization method for US forces [59]. The advantages of external fixation include facilitation of transportation of wounded patients with fractured extremities, allowing access to soft tissue wounds and thereby enabling effective wound care, and rapid stabilisation of the skeletal system to permit revascularisation procedures.…”
Section: Management Of Skeletal Injurymentioning
confidence: 99%
“…The current literature suggests that the favored tool for DCO in lower limbs is the application of external fixators. External fixations provide the advantages of decreased operating time, decreased blood loss and does not increase local complications besides not impairing the quality of definite osteosynthesis [20]. There are many types of extemal fixators, but the AD type tubular fixator is the commonest and most user friendly.…”
Section: Fracture Fixation : Damage Control Orthopedicsmentioning
confidence: 99%